The Courthouse Square in Texas - Veselka, Robert E. (University of Texas Press, 2021)
With its dignified courthouse set among shade trees and lawns dotted with monuments to prominent citizens and fallen veterans, the courthouse square remains the civic center in a majority of the county seats of Texas. Yet the squares themselves vary in form and layout, reflecting the different town-planning traditions that settlers brought from Europe, Mexico, and the United States. In fact, one way to trace settlement patterns and ethnic dispersion in Texas is by mapping the different types of courthouse squares. This book offers the first complete inventory of Texas courthouse squares, drawn from extensive archival research and site visits to 139 of the 254 county seats. Robert Veselka classifies every existing plan by type and origin, including patterns and variants not previously identified. He also explores the social and symbolic functions of these plans as he discusses the historical and modern uses of the squares. He draws interesting new conclusions about why the courthouse square remains the hub of commercial and civic activity in the smaller county seats, when it has lost its prominence in others